Aggregate emission intensity targets: Applications to the Paris Agreement. (Economic Inquiry, 2022)
We develop the concept of aggregate emission targets, which are cost effectively implemented national emission goals, and welfare rank expected‐emission‐equivalent aggregate emission intensity, quantity, and price targets. As targets become more stringent, it is more likely that the intensity target dominates the quantity target. A higher correlation between a country's gross domestic product and emission intensity favors aggregate intensity over price and quantity targets. Concerns about global welfare favor the aggregate quantity target. Applying the ranking conditions to the top 12 CO2 emitting nations, we obtain a robust finding that aggregate intensity targets dominate quantity targets for most of them.